(untitled) (Research, Society and Development, 2024)
Cerebral palsy (CP) is defined as a group of permanent disorders of the development of movement and posture, causing limitations in functional activities attributed to non-progressive disorders, which usually occur during the development of the fetal or infant brain. Its prevalence is estimated in Brazil at approximately 7 per 1000 live births. Changes in gastrointestinal and orofacial motility impose an increased risk of malnutrition on these children. Objective: The main objective of this review was to describe the importance of screening and nutritional assessment tools in this population. Methodology: A narrative literature review was carried out, using the PICO search strategy, using the guiding question: “Can nutritional screening tools during admission help in diagnosing nutritional risk in children with cerebral palsy?” Results: Although there are no specific screening tools for this population, STRONG Kids has been widely used, with results similar to anthropometry findings. Still, this is a population at risk, which requires periodic monitoring and the use of specific curves for CP.